Direct measurement of the round window niche dimensions using a 3‐dimensional moulding technique – a human cadaveric temporal bone study. (December 2015) - Shakeel, M.; Spielmann, P.M.; Jones, S.E.; Hussain, S.S.M.
Abstract : Objectives: To directly measure the various dimensions of the RWN focusing on the bony overhang and the vertical height between the free margin of the bony overhang and floor of the niche. Design: Laboratory‐based anatomical study using formalin‐preserved human cadaveric temporal bones. Setting: Temporal Bone laboratory, Department of Otolaryngology University of Dundee Medical School & Ninewells Hospital, Dundee, UK. Participants: NA. Main outcome measures: Three measurements were carried out (i) the depth of the round window niche extending from the free margin of the bony overhang to the fundus; (ii) vertical height from the free margin of the overhang to the floor of the niche (entrance) and (iii) the antero‐posterior (AP) dimension of the niche. Results: Based on mould technique, the three dimensions were calculated as follows: mean bony overhang = 2.1 mm (range 1.9–2.4 mm), height of RWN = 2.0 mm (1.8–2.15 mm) and AP length = 4.0 mm (3.3–4.95 mm). Conclusions: Our data demonstrate that the mean dimension of the bony overhang superior to the RWM is 2.1 mm.